SPIRITUAL THERAPY IN BREAST CANCER PATIENTS : SCOPING REVIEW - Zakariyati, Ariyanti Saleh*, Prihantonod, Erfina, Abdul Thalib (Chelonian Research Foundation, 2023)
Introduction : The increase in the number of cases of breast cancer both in the world and in Indonesia in particular is certainly a problem in itself. Breast cancer patients undergoing chemotherapy/radiotherapy treatment often experience decreased quality of life, anxiety and several other accompanying problems. The aim of this literature review is to see how spiritual therapy can improve the quality of life, reduce anxiety and stress in breast cancer patients. Methods : The literature search was a scoping review, which involved searching related articles from databases such as Pubmed, ScienceDirect, and the Cochrane Library over the last decade (2013-2022) using the boolean "OR" and "AND" with the keywords breast cancer, spirituality, religion and intervention With inclusion criteria, articles about breast cancer that receive spiritual/religious intervention. Results : There are 3 relevant articles according to the inclusion criteria and discussing spiritual therapy interventions for breast cancer patients. Interventions are carried out on patients while they are undergoing treatment at the hospital in the form of prayer and there are 2 articles that help/guide patients to strengthen their faith and pray for themselves. Conclusions: The spiritual needs of breast cancer patients impacts their overall well-being, improves coping mechanisms, lowers stress and increases productivity of breast cancer patients. Keywords : Spiritual therapy, Breast cancer, Coping, Stres, Quality of life